Keep using day-to-day tools in the classroom - Daradkeh, Yousef (2017)
We are in a networked world, where computers and its applications and other digital facilities take part of most human activities. Considering the use of electronic email or taking advantage of search engines and services as Google, it render to be almost impossible to not interact with any of such digital applyances each day of our lifes. If this is a reality to many of us, that born before the availablility of computers and networks, for the millennials and the youngters, even the most basic interaction between them are been made using mobile devices and other advanced communications and media systems. The impact on how such new advanced users experience the world as yet not reached most of the traditional schools, and higher education in particular whose needed to deal with huge challenges to cope with such a digital world. This sets the classroom as a strong candidate to suffer innovative approaches in order to keep its main role in the educational system.